Power sharing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
In several regions of the world, ranging from western Europe to southern Africa, so-called pools have been established where one country s surplus in power generation can be exported to another which needs more than it can produce. The southern...